Адаптивная система диагностики на основе нечетких отношений - Ротштейн, А.П.; Ракитянская, А.Б. (Кибернетика и системный анализ, 2009)
Causes (diagnoses) are retrieved and identified using observed effects (symptoms) based on fuzzy relations and Zadeh’s compositional rule of inference. An approach to designing adaptive fuzzy diagnostic systems is proposed. It allows solving fuzzy relational equations and designing and adjusting fuzzy relations using expert and experimental information.